OPTIMALISASI PEMANFAATAN BUNGKIL INTI SAWIT, GAPLEK DAN ONGGOK MELALUI TEKNOLOGI FERMENTASI DENGAN KAPANG BERBEDA SEBAGAI BAHAN PAKAN AYAM PEDAGING - Sukaryana, Yana; Nurhayati, Nurhayati; Wirawati, Chandra Utami (Jurnal Penelitian Pertanian Terapan, 2013)
The study was conducted at the Laboratory of Department of Animal Husbandry and Animal Cage, Lampung State Polytechnic. Object of study was fermented a mixture of palm kernel cake (PKC) and cassava (C), and a mixture of palm kernel cake (PKC) cassava byproduct (CBP) then to broilers applied. Fermentation research designed using completely randomized design factorial 2x2x6. The first factor was type of mold (Trichoderma viride and Aspergillus niger), a mixture of both of the second factor (PKC versus C and PKC versus CBP), and the third factor of mixture balance (100% PKC : 0% C or CBP, 80% PKC : 20% C or CBP, 60% PKC : 40% C or CBP, 40% PKC : 60% C or CBP, 20% PKC : 80% C or CBP, serta 0% PKC : 100% C or CBP). The results was applied to the broiler, completely randomized design with a 4x4 factorial pattern, the first kind of fermented best for each type of mold and the mixture of substances, the second factor in the level of use of fermented feed, namely 0, 10, 20, and 30%. The results of fermentation balance best mix: a) Trichoderma viride + PKC(60%) + C(40%) b) Trichoderma viride + PKC(80%) + CBP(20%), c) Aspergillus niger + PKC(60 %) + C (40%), d) Aspergillus niger + PKC(80%) + CBP(20%). Application results in broilers, namely: a) the use of a mixture of fermented counterpart [Trichoderma viride + PKC(60%) + C(40%)] with a level of 10% resulted in body weight (1342,67g), feed conversion (1,79), carcass weight (989,00) is the best, b) the use a mixture of fermented counterpart [Trichoderma viride + PKC(80%) + CBP(20%)] with a level of 20% resulted in a body weight (1334.67 g), feed conversion ratio (1,80), carcass weight (989,00 g) is the best, c) the use of a mixture of fermented counterpart [Aspergillus niger + PKC(60%) + C(40%)] with a level of 10% resulted in body weight (1408,67 g), feed conversion ratio (1,71), carcass weight (952,00 g) is the best, d) the use of a mixture of fermented counterpart [Aspergillus niger + PKC(80%) + CBP(20%)] with a level of 10% resulted in body weight (1357,00 g), feed conversion (1,77), carcass weight (923,00) is the best. Keywords: Palm kernel cake, cassava byproduct, cassava, Trichoderma viride, Aspergillus niger.